Church of Our Lady of Fatima, Laventille, Trinidad, W.I. - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2010)
Image depicts a frontal view of the Church of Our Lady of Fatima, located in the town of Laventille, on the outskirts of the capital city of Port of Spain, Trinidad, in the Republic of Trinidad and Tobago. Postcard numbered DT-77823-B.
Colour: Shades of Blue, Green, Yellow, Brown and Gray; Style: Portrait; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Catholic church buildings--Trinidad and Tobago; Church buildings--Trinidad and Tobago; Church architecture--Trinidad and Tobago